CSU Tufte Oval 1920-1924 - Campbell, Jessica, artist (Colorado State University. Libraries, 2016)
Tufte inspired digital recreation of the Oval inspired by Tufte's concepts of visualization.
Keywords: The Oval; CSU; Tufte; visualization